Activation of organic reactions by perchlorates - Deshpande, Suvarna S.; Kumar, Anil (Advances in Organic Synthesis, 2005)
Perchlorates have been frequently employed to promote a variety of synthetic transformations under ambient conditions. For example, the LiClO4-diethyl ether solvent medium has proven to be a powerful substitute for external high pressure for Diels-Alder reactions and other organic reactions. In this chapter are discussed several such organic transformations where perchlorates have played highly significant role in promoting their rates and yields.

Activity and stability of alpha-chymotrypsin in biocompatible ionic liquids: enzyme refolding by triethyl ammonium acetate - Attri, Pankaj; Venkatesu, Pannuru; Kumar, Anil (Physical Chemistry Chemical Physics, 2011)
In view the of wide scope of structural information of biomolecules in biocompatible ionic liquids (ILs) in various applications including chemical and biochemical, it is essential to study the productive preferential interactions between biological macromolecules and biocompatible ILs. We have therefore explored the stability and activity of alpha-chymotrypsin (CT) in the presence of five ILs from different families, such as triethyl ammonium acetate (TEAA), triethyl ammonium phosphate (TEAP) from ammonium salts, 1-benzyl-3-methylimidazolium chloride ([Bzmim][Cl]), 1-benzyl-3-methylimidazolium tetrafluoroborate ([Bzmim][BF(4)]) from imidazolium salts and tetra-butyl phosphonium bromide (TBPBr) from phosphonium families. Circular dichroism (CD) and UV-vis spectrophotometer experiments were used to study CT stabilization by ILs, related to the associated structural changes and enzyme activity studies, respectively. We observed that all ILs have a dominant contribution to the stabilization of CT. The stability and activity of CT depends on the structural arrangement of the ions of ILs. Our experimental results explicitly elucidate that more hydrophobic imidazolium and phosphonium cations carrying longer alkyl chains of ILs ([Bzmim][Cl], [Bzmim][BF(4)] and TBPBr) were weak stabilizers for CT, while small alkyl chain molecules of triethyl ammonium salts (TEAA and TEAP) are strong stabilizers and therefore more biocompatible for CT stability. Our CD and NMR measurements reveal that TEAA is a refolding additive for CT from a quenched thermal unfolded enzyme structure.

Atypical energetic and kinetic course of excited-state intramolecular proton transfer (ESIPT) in room-temperature protic ionic liquids - Manna, Arpan; Sayed, Mhejabeen; Kumar, Anil; Pal, Haridas (Journal of Physical Chemistry B, 2014)
The excited-state intramolecular proton-transfer (ESIPT) process in 1,8-dihydroxyanthraquinone (18DHAQ) dye has been investigated in protic ionic liquid (PIL) solvents using photochemical measurements. The results demonstrate noteworthy modulations in both steady-state and time-resolved emission characteristics of excited normal (N*) and tautomeric (T*) forms of the dye. That the emission of T* increases unexpectedly upon increasing solvent viscosity indicates that subsequent to the initial forward ESIPT, there is also a relatively slower back ESIPT process involved for the excited dye. It is inferred that the propensity of this back ESIPT process is determined by the dynamics of the diffusive solvent relaxation, a process that is known to be strongly viscosity-dependent in ionic liquids. Evidence of both forward and back ESIPT for the dye has been obtained from femtosecond fluorescence up-conversion measurements. While an unusually fast forward ESIPT is clearly observed in all of the PILs studied, the uncommon back ESIPT process is distinctly indicated in PIL solvents having lower viscosities, certainly due to reasonably fast diffusive solvent relaxation in these solvents that causes a temporal modulation in the energies of the normal and tautomeric forms within a reasonably short time and thereby brings down the energy of N* compared to that of T*, triggering the back ESIPT process. Observation of solvent-viscosity-dependent back ESIPT is an intriguing finding for the present study as to the best of our knowledge, such a behavior has so far not been reported in the literature for the ESIPT reaction.